PERFORMANCE OF SUKOHARJO POLICE MEMBERS REVIEWED FROM COMPETENCE AND ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION MEDIATION - Winarno, Eko; Istiatin, Istiatin; Sudarwati, Sudarwati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
This study aims to see the influence of competence and organizational commitment on performance with job satisfaction as a mediator. This study uses a non-experimental descriptive quantitative method with a survey and cross-sectional design. The unit of analysis of this study uses individual answers that represent their respective opinions, in this case members of the Polri Polres Sukoharjo which will be analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). In this study, the independent variables used are competence (X1) and organizational commitment (X2) and the dependent variable used is performance (Y). In this study, the intervening/mediating variable used is job satisfaction (M). The population in this study were 108 members of the Polri Polres Sukoharjo and then they would become research respondents who would provide answers to the statement items given. This study uses a small sample in a certain group so that the minimum sample that must be met is 70 respondents. The data collection methods used in this study are observation, documentation, questionnaires and literature studies. The data analysis technique used in this study uses Structural Equation Modeling-Partial Least Square (SEM-PLS). The conclusion from the results of testing, analysis and discussion in the previous chapter is that Competence does not affect job satisfaction in members of the Sukoharjo Police Department, Organizational commitment, Job satisfaction, Competence affects the performance of members of the Sukoharjo Police Department. Organizational commitment does not affect the performance of members of the Sukoharjo Police Department. Job satisfaction does not mediate the relationship between competence and the performance of members of the Sukoharjo Police Department. Job satisfaction does not mediate the relationship between organizational commitment and the performance of members of the Sukoharjo Police Department.